2012
DOI: 10.5152/akd.2012.061
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of echocardiographic epicardial fat thickness with severity of coronary artery disease-an observational study

Abstract: Objective: Epicardial fat is an indirect contact with coronary arteries. There are some studies about the relationship between this fat and metabolic syndrome and it has considered as an indicator of cardiovascular risk. Several studies have addressed the association between epicardial fat thickness (EFT) and coronary artery disease (CAD) with conflicting results. The aim of our study was to evaluate the hypothesis that echocardiographic EFT thickness could be a marker severe CAD. Methods: Overall, 315 cases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 34 publications
1
37
2
3
Order By: Relevance
“…This point was in contrast with the findings of a study undertaken by Mookadam et al However, it seems that age was a noteworthy confounding variable in the aforementioned study (12). We also could not establish a relation between the amount of EFT and extent of coronary involvement, as opposed to several other studies, that have proposed an association between EFT and severity of CAD (4,5). This issue might be explained, based on different baseline characteristics across various study populations and the age, as an important variable affecting the expansion of atherosclerosis, which was also mentioned in Jeong study (4).…”
Section: Discussioncontrasting
confidence: 70%
“…This point was in contrast with the findings of a study undertaken by Mookadam et al However, it seems that age was a noteworthy confounding variable in the aforementioned study (12). We also could not establish a relation between the amount of EFT and extent of coronary involvement, as opposed to several other studies, that have proposed an association between EFT and severity of CAD (4,5). This issue might be explained, based on different baseline characteristics across various study populations and the age, as an important variable affecting the expansion of atherosclerosis, which was also mentioned in Jeong study (4).…”
Section: Discussioncontrasting
confidence: 70%
“…Inflammatory mediators originating from epicardial fat tissue may induce some compositional changes in atherosclerotic plaques, induce atherosclerosis and influence plaque progression and composition. Shemirani et al [26] reported that Califf scores, which reflect the severity of CAD depending on the myocardium at risk, were correlated with EFT. In contrast to that study, we excluded patients with the acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiographic EAT measurement is a non-invasive and simple way to measure location-specific EAT at the right ventricular free wall clinically [12-17]. Alternatively, CT (computed tomography) or MRI (magnetic resonance imaging) can also provide the simple but precise 2D measurement in the thickness of EAT in all cardiac segments [11,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence about the association between location-specific EAT thickness at the right ventricular free wall and coronary artery disease (CAD) is still controversial. Several studies using echocardiography have demonstrated a significant relationship between CAD and location-specific EAT thickness measured at right ventricular free wall [13,14,16,17], while some studies using echocardiography or CT failed to observe a significant association [11,12,19,20]. Recent evidence has suggested that there is increasing attention on location-specific EAT thickness at the left AV groove as a potentially new biomarker associated with cardiometabolic risks by using 2D CT or MR measurement [11,19,21,22].…”
Section: Introductionmentioning
confidence: 99%